Marine - Lenhart Syndrome: Pathogenesis, Clnical Classification and Diagnosis - Sánchez Beorlegui, Jesús (2000)
OBJETIVE: To determine the incidence of Marine-Lenhart syndrome (MLS) in the previously thyroidectomies reported and describe its epidemiology, symptoms, diagnosis methods and compare with Plummer syndrome (PS). MATERIALS AND METHODS: Medical records of 694 hyperthyroid patients were reviewed and ANOVA was perform to compare age of patients, time of disease and thyroid's weight between MLS (diffuse hyperthyroidism with at least 1 node with increased uptake and with or without cold nodes) and PS. RESULTS: The MLS was reported in 4,3% of hyperthyroidisins and 1,2% of the total. Patients age, time of disease and thyroids weight were significantly different between MLS and PS. MLS produced pressure symptoms in two thirds of the patients and functional sings and symptoms in the most of them. In fotir of our patients we fotind exoplitalmos and orily one developed thyroid carcinoma. Total thyroidectorny rendered similar parathyroid morbility rates to those observed with subtotal thyroidectoiny. CONCLUSIONS: MLS patients had more time of disease, functional and pressure symptoms were more frequently, were prone to develop exoplitalmos and total thyroidectorny was the treatment of choice.